(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
Programming departments often find it difficult to meet deadlines and deliver the product on par with the customer’s needs. To alleviate these issues, agile methods (AM) provide alternatives in project management, since they aim to optimize the software development process. This work aimed to identify the application of AMs in the Informatics Center of the Alto Vale do Itajaí (NIAVI). In the data collection technique to generate analyses regarding the adoption of AMs, virtual questionnaires were applied between June 9 and 13 with 19 questions to NIAVI member companies, the answers obtained were quantitatively analyzed. The results obtained were that none of the NIAVI companies uses AMs or any other method of software development.